Cohesion and Coherence of Sandiaga Uno’s Speech in The Event High-Level Thematic Debate on Tourism United Nation General Assembly 2022 - Solvandi, Yori; Raflis, Raflis (Jurnal Ilmiah Langue and Parole, 2024)
This research aims to describe the relationship between the form of cohesion and the meaning of coherence in the discourse analysis of Sandiaga Uno's Speech in the High Level Thematic Debate On Tourism United Nation General Assembly 2022. The frequency of use of cohesion markers and coherence varies in their use, in The subject of this study focused on sentences in speech texts.The theoretical research used in this research is Tarigan's theory which discusses aspects of cohesion and coherence. This research is the researcher himself with based on knowledge of theories regarding aspects of cohesion and coherence. This study used qualitative descriptive method Data were collected through observation methods. Then, the data is analyzed through the method of interpretive findings with the technique of collecting data taking notes techniques.The results showed that markers of cohesion and coherence were used in the script of Sandiaga Uno's speech. Shows the element of grammatical cohesion consists of elements of reference, subtitution, ellipsis, and conjuction. Then The lexical cohesion element consists of repetition, synonymy, antonymy, collocation. From the aspect of coherence observed through contradiction, contrast, and temporal coherence.